Reflexão sobre os desafios da pós-graduação: novas perspectivas sociais, conhecimento e poder - Bernardete Angelina Gatti (Associacao Nacional de Pós-Graduação e Pesquisa em Educação, 2001)
This article emphasises the differences between the historical moment in which postgraduate programmes (master and PhD) were created and the present one. It discusses the social role of these courses in the dichotomy knowledge x power and the dilemma faced by these programmes when urged by society to include innovative curricular modalities and to accept new student profiles in opposition to maintaining themselves as a field reserved for the chosen few. Based on considerations that the determinants of social inequalities include different opportunities of access to and appropriation of knowledge, the article poses a challenge to the present model of postgraduate studies: to revise its social role, values and curriculum in order to attend a different type of public, with diverse interests.